(untitled) (Research, Society and Development, 2021)
When investigating such a problem, the objective is to notice it occurs, absorbing it in a critical and perceptible way to the scientific theoretical understanding. The work is important to understand the concrete configuration of this problem and its observation in the professional, social and technical environment in which its categories are presented. The objective is to identify pharmaceutical interventions as practices that make a difference. too relevant for training to understand how it happens. Therefore, it seeks to elucidate questions that are asked in this aspect. It justifies the creation of texts that can show how it happens, and its importance in the face of studies on professional training, in addition to enabling further discussions on concepts, categories and aspects of application to the field of intervention. Thus, through a brief literature review, this theme is studied, instilling it in the thoughts of the contemporary context that update it in response to our greatest curiosities about such an occurrence.